Three-dimensional porous microarray of gold modified electrode for ultrasensitive and simultaneous assay of various cancer biomarkers - Shi, L.; Chu, Z.; Liu, Yu; Peng, J.; Jin, W. (R S C Publications, 2014)
A three-dimensional (3D) microarray of a gold modified electrode with a nanoporous surface was successfully fabricated in this work. The special gold micro/nanostructure possessed an extremely high surface area (ca. 20 times its geometrical area), as well as highly stable and easily chemically modified properties, which could distinctly increase the binding sites for biological probes, facilitate the diffusion profile and enhance the electron transfer. Owing to these advantages, an ultrasensitive biosensor was designed on the porous microarray of the gold modified electrode (PMGE), which realized the simultaneous assay of cancer biomarkers of angiogenin (Ang) and thrombin (Tob). Under optimal experimental conditions, an impressively ultralow detection limit of 0.07 pM for Ang (a linear range from 0.2 pM to 10 nM) and a limit of 20 fM for Tob (a linear range from 50 fM to 5 nM) were obtained. Besides, the fabricated biosensor showed an excellent stability, good reproducibility and a high selectivity towards other biological proteins, which also exhibited promising potential for the application in a real serum sample analysis. Such a micro/nanostructure of gold could have widespread applications in biological sensing and quantitative biochemical analysis.